Navigating the Effectiveness of Authentic Reading Materials Toward ESP University Students’ Reading Proficiency - Setyowati, Yulis; Astutik, Ari; Duwila, Shanty Duwila AYPS (Indo-MathEdu Intellectuals Journal, 2023)
The field of ESP teaching has undergone a revolutionary transformation with the integration of ICT tools and other authentic materials. These resources have proven to be invaluable to learners as they enable real-life interactions with native speakers. Various studies have explored the challenges faced by teachers and learners in ESP teaching situations. Therefore, this paper aims to describe the effectiveness of reading authentic materials toward the reading proficiency of psychology department students.   The study was conducted at the Psychology Department of Universitas Wijaya Putra. The students participated in 14 meetings, during which the experimental group was exposed to authentic reading materials and the control cluster received streamlined materials, a pre-test and post-test of the reading comprehension test were given to the students. The marks obtained were analyzed using SPPS and the students were given a set of tasks that included 50 multiple-choice questions and 10 essay questions. The research results revealed that the mean deviation score for the experimental group was 80, while it was 65 for the control group. Consequently. This provides evidence supporting the acceptance of the hypothesis, indicating an improvement in student performance after receiving the treatment. Specifically, the results revealed that exposure to authentic materials improved the reading proficiency of psychology department students